The effect of argumentation-oriented learning models, inquiry-based learning models and science process skills on students' argumentation ability in chemistry - Nurul Rahmiah Fitri; Muhammad Rusdi; Muhammad Haris Effendi-Hasibuan (Pascasarjana Universitas Negeri Medan, 2022)
One of the models whose learning syntax matches the science process skill component and students' argumentation ability is the inquiry model. Inquiry models have been widely applied, such as Guided Inquiry Based Learning (GIBL), and modified, such as the Argument Driven Inquiry (ADI) and Argumentative Inquiry Blended Learning (AIBL) learning models, where the ADI and AIBL learning models in the learning syntax have been integrated with argumentation activities. The purpose of this study was to examine the effect of learning models and students' science process skills on students' argumentation ability. The research design used a 3 x 2 factorial design with a mixed method. The results showed that: (1) there was an effect of argumentation-oriented learning on the inquiry learning models on students' argumentation ability; (2) there is an effect of science process skill level on students' argumentation ability; and (3) there is no interaction between argumentation-oriented learning on the inquiry learning models and the level of science process skill on students' argumentation ability.Keywords: Argumentation ability; Argument driven inquiry; Argumentative inquiry blended learning; Guided inquiry-based learning; Science process skills